Psoriasis In Eastern Nepal : Clinical Profile And Patient′s Beliefs About The Disease - Agrawal Sudha; Garg Vijay Kumar; Agarwalla Arun; Shyangwa Promod M (Wolters Kluwer Medknow Publications, 2003)
The purpose of the study was to know the clinical profile of psoriasis and also to assess patientâ€s beliefs about their disease. A total of 210 patients with psoriasis was studied. The patients above 16 years of age were also subjected to Illness Perception Questionnaire (IPQ). Psoriasis vulgaris was the commonest type of psoriasis. The strongest belief of the patients in the causation of psoriasis was germs or virus (74.8%). A Majority of patients believed that psoriasis had a major consequence on their lives (81.4%) and that psoriasis was a serious condition (82.9%). Women were significantly more likely to believe that their psoriasis had severe consequences on their lives. The majority of patients believed their psoriasis was more likely to be chronic (63.8%) or recurrent (70.8%). Eighty percent of patients believed that their psoriasis would improve with time and 82.9% believed that there was a lot that they themselves could do to control their condition. The most commonly reported symptoms were â€skin flakingâ€ (89.5%) followed by â€itchingâ€ (81%). The overall PASI was not associated with patientâ€s beliefs.